Near-infrared spectroscopy and mathematical modeling for the characterization of human cerebral hemodynamics in the microvasculature - Tgavalekos, Kristen. (2018)
Abstract: Near-infrared spectroscopy (NIRS), in combination with coherent hemodynamics spectroscopy (CHS), provides information about the cerebral microvasculature in terms of cerebral blood flow, cerebral blood volume, and the cerebral metabolic rate of oxygen. We characterize the frequency-dependent relationship between tissue concentrations of oxyhemoglobin and deoxyhemoglobin, measured with NIRS, as well as the relationship between total hemoglobin concentration and arterial blood pressure in healthy subjects. We use the hemodynamic model of CHS for the analysis of the results to yield physiologic parameters such as absolute cerebral blood flow and cerebral autoregulation. Further, we demonstrate the application of NIRS-CHS in the clinical setting of the neurocritical care unit.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Sergio Fantini.; Committee: Irene Georgakoudi, Brian Tracey, and Joshua Kornbluth.; Keyword: Biomedical engineering.